Solid electrolyte sheet and method for producing same
By forming a second solid electrolyte layer of a porous layer on the first solid electrolyte layer of the solid electrolyte sheet, the problem of shrinkage during the firing process is solved, and the operability and strength of the solid electrolyte sheet are improved.
Patent Information
- Application Number
- CN202380063369.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-02
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-11
AI Technical Summary
During the firing process of solid electrolyte sheets, shrinkage is prone to occur, resulting in a decrease in the operability and strength of the sheets.
By forming a second solid electrolyte layer of porous layer on at least one main surface of the first solid electrolyte layer, a slurry is prepared by using a solid electrolyte powder and a polymer powder of different average crystal particle sizes, an organic carrier with an adhesive added to prepare a binder, and is dried and fired to form a laminate to suppress shrinkage.
It effectively suppresses the shrinkage phenomenon during the firing process of solid electrolyte sheets, improves the operability and strength of the sheets, and avoids ups and downs and warping.
Smart Images

Figure CN119816972A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for manufacturing a solid electrolyte sheet and the solid electrolyte sheet. Background Art
[0002] Lithium-ion secondary batteries have established their position as high-capacity and lightweight power sources that are indispensable for mobile devices, electric vehicles, etc. However, in existing lithium-ion secondary batteries, flammable organic electrolytes are mainly used as electrolytes, so there are concerns about dangers such as fire. As a solution to this problem, people are promoting the development of lithium-ion all-solid-state batteries that use solid electrolytes instead of organic electrolytes. In addition, lithium has problems such as the rise in global raw materials, so the development of all-solid-state sodium-ion batteries is also being promoted.
[0003] In the following patent document 1, an all-solid-state secondary battery is disclosed, which includes a solid electrolyte sheet and an electrode layer formed on the surface of the solid electrolyte sheet. Patent document 1 records that the solid electrolyte sheet is formed by forming a second solid electrolyte layer on at least one surface of a first solid electrolyte layer. In addition, patent document 1 records that the second solid electrolyte layer is a porous solid electrolyte layer.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent document 1: International Publication No. 2021 / 045039. Summary of the invention
[0007] Problem that the invention aims to solve
[0008] However, in order to form a solid electrolyte sheet, for example, when a green sheet method is used, shrinkage may occur during firing accompanied by densification. In addition, when the solid electrolyte sheet is extremely thin, shrinkage may occur unevenly within the surface, causing undulations and warping. In this case, the handleability and strength of the solid electrolyte sheet may be reduced.
[0009] An object of the present invention is to provide a method for producing a solid electrolyte sheet and a solid electrolyte sheet capable of suppressing shrinkage of the sheet during a firing step when the solid electrolyte sheet is formed.
[0010] Technical solutions to the problem
[0011] A method for producing a solid electrolyte sheet and various aspects of the solid electrolyte sheet that solve the above-mentioned problems will be described.
[0012] The solid electrolyte sheet of mode 1 of the present invention is characterized in that it includes: a first solid electrolyte layer as a dense layer; and a second solid electrolyte layer as a porous layer arranged on a main surface of at least one side of the first solid electrolyte layer, and the average crystal particle size of the first solid electrolyte constituting the first solid electrolyte layer is smaller than the average crystal particle size of the second solid electrolyte constituting the second solid electrolyte layer.
[0013] In the solid electrolyte sheet of aspect 2, preferably, in aspect 1, the second solid electrolyte layer is provided on both main surfaces of the first solid electrolyte layer.
[0014] In the solid electrolyte sheet of aspect 3, preferably, in aspect 1 or aspect 2, the average crystal grain size of the first solid electrolyte is 0.01 μm or more and 10 μm or less.
[0015] In the solid electrolyte sheet of aspect 4, preferably, in any one of aspects 1 to 3, the average crystal grain size of the second solid electrolyte is 0.1 μm or more and 100 μm or less.
[0016] The solid electrolyte sheet of aspect 5 is characterized in that, in any one of aspects 1 to 4, the first solid electrolyte layer and the second solid electrolyte layer are integrated, and the thickness of the second solid electrolyte layer is thicker than the thickness of the first solid electrolyte layer.
[0017] In the solid electrolyte sheet of aspect 6, preferably, in any one of aspects 1 to 5, the second solid electrolyte layer has pores having a diameter larger than a thickness of the first solid electrolyte layer.
[0018] In the solid electrolyte sheet of aspect 7, preferably, in any one of aspects 1 to 6, the diameter of the pores present in the second solid electrolyte layer is 0.1 μm or more and 100 μm or less.
[0019] In the solid electrolyte sheet of aspect 8, preferably, in any one of aspects 1 to 7, the porosity of the second solid electrolyte layer is 25% or more and 97% or less.
[0020] In the solid electrolyte sheet of mode 9, preferably, in any one of modes 1 to 8, at least one of the first solid electrolyte layer and the second solid electrolyte layer contains at least one selected from the group consisting of β″-alumina, β-alumina and NASICON crystals.
[0021] In the solid electrolyte sheet of aspect 10, preferably, in any one of aspects 1 to 9, the solid electrolyte sheet is used for an all-solid-state sodium ion secondary battery.
[0022] The method for manufacturing a solid electrolyte sheet of mode 11 of the present invention is a method for manufacturing a solid electrolyte sheet, the solid electrolyte sheet comprising: a first solid electrolyte layer as a dense layer; and a second solid electrolyte layer as a porous layer arranged on a main surface of at least one side of the first solid electrolyte layer, the method for manufacturing a solid electrolyte sheet is characterized in that it comprises: (a) for a powder of at least one of a first solid electrolyte powder and a raw material powder of the first solid electrolyte powder, an organic carrier containing a binder is added to prepare a slurry, the slurry is applied on a substrate and dried, thereby obtaining a raw sheet for forming a first solid electrolyte layer; (b) for a powder of at least one of a second solid electrolyte powder and a raw material powder of the second solid electrolyte powder and a polymer (c) a process of laminating the second solid electrolyte layer forming raw sheet on the main surface of at least one side of the first solid electrolyte layer forming raw sheet to obtain a laminate; and (d) a process of forming the first solid electrolyte layer as a dense layer and forming the second solid electrolyte layer as a porous layer by firing the laminate, wherein the average particle size of at least one of the first solid electrolyte powder and the raw material powder of the first solid electrolyte powder is smaller than the average particle size of at least one of the second solid electrolyte powder and the raw material powder of the second solid electrolyte powder.
[0023] In the method for producing a solid electrolyte sheet according to aspect 12, preferably, in aspect 11, the second solid electrolyte layer is formed on both main surfaces of the first solid electrolyte layer.
[0024] In the method for manufacturing a solid electrolyte sheet of embodiment 13, preferably, in embodiment 11 or embodiment 12, the average particle size of at least one of the first solid electrolyte powder and the raw material powder of the first solid electrolyte powder is 0.01 μm or more and 10 μm or less.
[0025] In the method for manufacturing a solid electrolyte sheet of mode 14, preferably, in any one of modes 11 to 13, the average particle size of at least one of the second solid electrolyte powder and the raw material powder of the second solid electrolyte powder is greater than 0.1 μm and less than 100 μm.
[0026] In the method for producing a solid electrolyte sheet according to aspect 15, preferably, in any one of aspects 11 to 14, the polymer powder has an average particle size of 0.1 μm or more and 100 μm or less.
[0027] In the method for manufacturing a solid electrolyte sheet of method 16, preferably, in any one of methods 11 to 15, the mixing ratio of the second solid electrolyte powder and at least one of the raw material powders of the second solid electrolyte powder to the polymer powder is 75:25 to 3:97 in volume ratio.
[0028] In the method for manufacturing a solid electrolyte sheet of mode 17, it is preferred that in any one of modes 11 to 16, at least one of the first solid electrolyte layer and the second solid electrolyte layer contains at least one selected from the group consisting of β″-alumina, β-alumina and NASICON crystals.
[0029] In the method for producing a solid electrolyte sheet according to aspect 18, preferably, in any one of aspects 11 to 17, the solid electrolyte sheet is used for an all-solid-state sodium ion secondary battery.
[0030] Effects of the Invention
[0031] According to the present invention, it is possible to provide a method for producing a solid electrolyte sheet and a solid electrolyte sheet capable of suppressing shrinkage of the sheet in a firing step when the solid electrolyte sheet is formed. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 (a) to (d) are schematic cross-sectional views for explaining the details of each step in the method for producing a solid electrolyte sheet according to one embodiment of the present invention.
[0033] Figure 2 This is a schematic cross-sectional view showing a solid electrolyte sheet according to one embodiment of the present invention.
[0034] Figure 3 This is a scanning electron microscope photograph of the surface of the solid electrolyte sheet produced in Example 1 at a magnification of 500 times.
[0035] Figure 4 This is a scanning electron microscope photograph of a cross section of the solid electrolyte sheet produced in Example 1 at a magnification of 500 times.
[0036] Figure 5 This is a scanning electron microscope photograph of a cross section of the solid electrolyte sheet produced in Example 1 at a magnification of 2000 times.
[0037] Figure 6 These are photographs showing the appearance of the solid electrolyte sheet produced in Example 1 before and after firing.
[0038] Figure 7 This is a scanning electron microscope photograph of a cross section of a solid electrolyte sheet produced in Comparative Example 2 at a magnification of 500 times.
[0039] Figure 8 These are photographs showing the appearance of the solid electrolyte sheet produced in Comparative Example 1 before and after firing.
[0040] Fig. 9 This is a scanning electron microscope photograph of a cross section of the first solid electrolyte layer of the solid electrolyte sheet produced in Example 1 after thermal etching, at a magnification of 10,000 times.
[0041] Fig.10 This is a scanning electron microscope photograph of a cross section of the second solid electrolyte layer after thermal etching of the solid electrolyte sheet produced in Example 1, at a magnification of 10,000 times. DETAILED DESCRIPTION
[0042] Hereinafter, preferred embodiments will be described. However, the following embodiments are merely illustrative, and the present invention is not limited to the following embodiments. In addition, in each of the drawings, components having substantially the same function are sometimes referred to with the same reference numerals.
[0043] [Method for producing solid electrolyte sheet]
[0044] The method for manufacturing a solid electrolyte sheet of the present invention is a method for manufacturing a solid electrolyte sheet, which includes: a first solid electrolyte layer as a dense layer; and a second solid electrolyte layer as a porous layer provided on at least one main surface of the first solid electrolyte layer.
[0045] The method for producing a solid electrolyte sheet of the present invention includes the following steps (a) to (d).
[0046] (a) A step of adding an organic vehicle containing a binder to at least one of a first solid electrolyte powder and a raw material powder of the first solid electrolyte powder to prepare a slurry, applying the slurry on a substrate, and drying the slurry to obtain a green sheet for forming a first solid electrolyte layer.
[0047] (b) A process for preparing a slurry by adding an organic carrier containing a binder to a mixed powder of a powder containing a second solid electrolyte powder and at least one of the raw powders of the second solid electrolyte powder and a polymer powder, applying the slurry on a substrate and drying the mixed powder to obtain a raw sheet for forming a second solid electrolyte layer.
[0048] (c) A step of laminating a second solid electrolyte layer forming green sheet on at least one main surface of the first solid electrolyte layer forming green sheet to obtain a laminated body.
[0049] (d) A step of forming a first solid electrolyte layer as a dense layer and a second solid electrolyte layer as a porous layer by firing the laminated body.
[0050] In addition, in the present invention, the average particle size of at least one of the first solid electrolyte powder and the raw material powder of the first solid electrolyte powder is smaller than the average particle size of at least one of the second solid electrolyte powder and the raw material powder of the second solid electrolyte powder. For example, the average particle size of the first solid electrolyte powder may be smaller than the average particle size of the second solid electrolyte powder. In addition, the average particle size of the raw material powder of the first solid electrolyte powder may be smaller than the average particle size of the raw material powder of the second solid electrolyte powder.
[0051] The method for producing a solid electrolyte sheet of the present invention includes the above-mentioned structure, so that shrinkage of the sheet can be suppressed during the firing step when the solid electrolyte sheet is formed. This point can be explained as follows.
[0052] In the prior art, when forming a solid electrolyte sheet, for example, when a green sheet method is used, shrinkage may occur during firing accompanied by densification. In addition, when the solid electrolyte sheet is extremely thin, shrinkage may occur unevenly within the surface, causing undulations and warping. In this case, the handleability and strength of the solid electrolyte sheet may be reduced.
[0053] In contrast, in the method for producing a solid electrolyte sheet of the present invention, the second solid electrolyte layer as a porous layer is formed on at least one main surface of the first solid electrolyte layer as a dense layer, so that shrinkage of the sheet can be suppressed during the firing step.
[0054] However, if the second solid electrolyte layer as a porous layer is stacked on the first solid electrolyte layer as a dense layer and fired, the second solid electrolyte layer as a porous layer may be peeled off from the first solid electrolyte layer. As a result, the shrinkage of the first solid electrolyte layer may not be sufficiently suppressed.
[0055] In this regard, the inventors have discovered that by making the average particle size of at least one of the first solid electrolyte powder forming the first solid electrolyte layer and the raw material powder of the first solid electrolyte powder smaller than the average particle size of the second solid electrolyte powder forming the second solid electrolyte layer and at least one of the raw material powders of the second solid electrolyte powder, during the firing process, the second solid electrolyte layer as a porous layer can be made difficult to peel off from the first solid electrolyte layer, and the shrinkage of the obtained solid electrolyte sheet can be suppressed.
[0056] In addition, regarding this point, the following is considered. By setting the average particle size of the solid electrolyte powder (raw material powder) to the porous layer (second solid electrolyte layer)> the dense layer (first solid electrolyte layer), the shrinkage of the porous layer becomes relatively small, and the shrinkage of the laminate as a whole becomes equal to the shrinkage of the porous layer. In addition, it is believed that the dense layer becomes constrained by the porous layer with at least one main surface, so it is not easy to deform the shape, and corrugation and warping are suppressed.
[0057] Below, refer to Figure 1 (a) to (d) The details of each step in the method for producing a solid electrolyte sheet of the present invention are described.
[0058] (a) Preparation of Green Sheet for Forming First Solid Electrolyte Layer
[0059] First, a first solid electrolyte powder is prepared.
[0060] As the first solid electrolyte powder, for example, when the obtained solid electrolyte sheet is used for an all-solid-state sodium ion secondary battery, at least one selected from β″-alumina, β-alumina, and NASICON crystal can be prepared.
[0061] Specific examples of β″-alumina include trigonal (Al 10.35 Mg 0.65 O 16 )(Na 1.65 O), (Al 8.87 Mg 2.13 O 16 )(Na 3.13 O), Na 1.67 Mg 0.67 Al 10.33 O 17 、Na 1.49 Li 0.25 Al 10.75 O 17 、Na 1.72 Li 0.3 Al 10.66 O 17 、Na 1.6 Li 0.34 Al 10.66 O 17 wait.
[0062] Specific examples of β-alumina include hexagonal (Al 10.35 Mg 0.65 O 16 )(Na 1.65 O), (Al 10.37 Mg 0.63 O 16 )(Na1.63 O), NaAl 11 O 17 、(Al 10.32 Mg 0.68 O 16 )(Na 1.68 O) etc.
[0063] NASICON crystals preferably comprise the general formula Na s A1 t A2 u O v (A1 is at least one selected from Al, Y, Yb, Nd, Nb, Ti, Hf and Zr, A2 is at least one selected from Si and P, s = 1.4 to 5.2, t = 1 to 2.9, u = 2.8 to 4.1, v = 9 to 14) is a compound. Here, A1 is preferably at least one selected from Y, Nb, Ti and Zr. Thus, a crystal with better ion conductivity can be obtained.
[0064] In addition, the preferred ranges of the coefficients in the above general formula are as follows.
[0065] s is preferably 1.4 to 5.2, more preferably 2.5 to 3.5, and further preferably 2.8 to 3.1. If s is too small, the number of sodium ions decreases, so the ion conductivity of the solid electrolyte is easily reduced. On the other hand, if s is too large, the remaining sodium forms compounds such as sodium phosphate and sodium silicate that do not contribute to ion conduction, so the ion conductivity of the solid electrolyte is easily reduced.
[0066] t is preferably 1 to 2.9, more preferably 1 to 2.5, and further preferably 1.3 to 2. When t is too small, the three-dimensional network structure in the crystal is reduced, so the ion conductivity of the solid electrolyte is easily reduced. On the other hand, when t is too large, compounds such as zirconium oxide and aluminum oxide that do not contribute to ion conduction are formed, so the ion conductivity of the solid electrolyte is easily reduced.
[0067] u is preferably 2.8 to 4.1, more preferably 2.8 to 4, further preferably 2.9 to 3.2, and particularly preferably 2.95 to 3.1. If u is too small, the three-dimensional network structure in the crystal is reduced, so the ion conductivity of the solid electrolyte is easily reduced. On the other hand, when u is too large, crystals that do not contribute to ion conduction are formed, so the ion conductivity of the solid electrolyte is easily reduced.
[0068] v is preferably 9 to 14, more preferably 9.5 to 12, and further preferably 11 to 12. If v is too small, A1 (for example, aluminum component) becomes a low valence number, so the electrical insulation is easily reduced. On the other hand, if v is too large, it becomes an overoxidized state, and the sodium ions are bound by the lone pair of electrons of the oxygen atoms, so the ionic conductivity of the solid electrolyte is easily reduced.
[0069] The NASICON crystal is preferably a monoclinic crystal, a hexagonal crystal, or a trigonal crystal, and more preferably a monoclinic crystal or a trigonal crystal. In this case, the ion conductivity of the solid electrolyte can be further improved.
[0070] Specific examples of NASICON crystals include Na 3 Zr 2 Si 2 PO 12 、Na 3.2 Zr 1.3 Si 2.2 P 0.8 O 10.5 、Na 3 Zr 1.6 Ti 0.4 Si 2 PO 12 、Na 3 Hf 2 Si 2 PO 12 、Na 3.4 Zr 0.9 Hf 1.4 Al 0.6 Si 1.2 P 1.8 O 12 、Na 3 Zr 1.7 Nb 0.24 Si 2 PO 12 、Na 3.6 Ti 0.2 Y 0.8 Si 2.8 O 9 、Na 3 Zr 1.88 Y 0.12 Si 2 PO 12 、Na 3.12 Zr 1.88 Y 0.12 Si 2 PO 12 、Na 3.05 Zr 2 Si 2.06 P 0.95 O 12 、Na 3.4 Zr 2 Si 2.4 P 0.6 O 12 、Na 3.6 Zr 0.13 Yb1.67 Si 0.11 P 2.9 O 12 、Na 5 YS 4 O 12 Among them, NASICON crystal is preferably Na 3.12 Zr 1.88 Y 0.12 Si 2 PO 12 Or Na 3.05 Zr 2 Si 2.06 P 0.95 O 12 In this case, the sodium ion conductivity can be further improved.
[0071] In addition, as the first solid electrolyte powder, for example, when the obtained solid electrolyte sheet is used for an all-solid-state lithium-ion secondary battery, a solid electrolyte powder selected from La 0.51 Li 0.34 Ti 2.94 , Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 , Li 7 La 3 Zr 2 O 12 , Li 1.07 Al 0.69 Ti 1.46 (PO 4 ) 3 , Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 At least one of .
[0072] Alternatively, a raw material powder of the first solid electrolyte powder (powder that reacts in a subsequent firing step to become a solid electrolyte) may be prepared instead of the first solid electrolyte powder. Alternatively, a mixed powder of the first solid electrolyte powder and the raw material powder of the first solid electrolyte powder may be prepared.
[0073] As the raw material powder of the first solid electrolyte powder, for example, in the case of a raw material powder of β″-alumina, a powder containing 65% to 98% of Al in mol% can be prepared. 2 O 3 , 2%~20% Na 2 O, 0.3% to 15% MgO + Li 2O, 0% ~ 20% ZrO 2 , 0% ~ 5% Y 2 O 3 The reasons for limiting the composition as described above are described below.
[0074] Al 2 O 3 It is the main component of β"-alumina. 2 O 3 The content of Al is preferably 65% to 98% in mole %, more preferably 70% to 95%. 2 O 3 If Al 2 O 3 If the amount is too large, α-alumina which does not have sodium ion conductivity will remain, and the ion conductivity of the solid electrolyte is likely to decrease.
[0075] Na 2 O is a component that imparts sodium ion conductivity to the solid electrolyte. 2 The content of O in mole % is preferably 2% to 20%, more preferably 3% to 18%, and further preferably 4% to 16%. 2 If O is too little, it is difficult to obtain the above effect. 2 If there is too much O, the remaining sodium will form NaAlO 2 Since there are compounds that do not contribute to ion conductivity, the ion conductivity of the solid electrolyte is easily reduced.
[0076] MgO and Li 2 O is a component (stabilizer) that stabilizes the structure of β″-alumina. MgO+Li 2 The content of O is preferably 0.3% to 15% in mol%, more preferably 0.5% to 10%, and further preferably 0.8% to 8%. MgO+Li 2 When there is too little O, α-alumina remains in the solid electrolyte, and the ion conductivity is likely to decrease. 2 When there is too much O, MgO or Li 2 O remains in the solid electrolyte, and the ion conductivity is likely to decrease.
[0077] ZrO 2 and Y 2 O 3 It has the effect of suppressing abnormal grain growth of β"-alumina during firing and improving the adhesion of each particle of β"-alumina. As a result, the ion conductivity of the solid electrolyte is easily improved. ZrO 2The content of Y is preferably 0% to 20% in mole %, more preferably 0% to 15%, further preferably 1% to 13%, and particularly preferably 2% to 10%. 2 O 3 The content of ZrO is preferably 0% to 5% in terms of mole %, more preferably 0.01% to 4%, and even more preferably 0.02% to 3%. 2 or Y 2 O 3 If the amount is too large, the amount of β″-alumina produced decreases, and the ion conductivity of the solid electrolyte tends to decrease.
[0078] As the raw material powder of the first solid electrolyte powder, for example, in the case of a raw material powder of NASICON crystal, a powder containing 17.5% to 50% of Na in mol% can be prepared. 2 O, 12% to 45% Al 2 O 3 +Y 2 O 3 +Yb 2 O 3 +Nd 2 O 3 +Nb 2 O 5 +TiO 2 +HfO 2 +ZrO 2 24%~54% SiO 2 +P 2 O 5 of raw material powder.
[0079] As described above, the average particle size of at least one of the first solid electrolyte powder and the raw material powder of the first solid electrolyte powder is smaller than the average particle size of at least one of the second solid electrolyte powder and the raw material powder of the second solid electrolyte powder.
[0080] The average particle size of at least one of the first solid electrolyte powder and the raw material powder of the first solid electrolyte powder is preferably 0.01 μm or more, more preferably 0.05 μm or more, further preferably 0.1 μm or more, preferably 10 μm or less, more preferably 5 μm or less, further preferably 3 μm or less, further preferably 1 μm or less, and particularly preferably 0.6 μm or less. In this case, in the subsequent firing step, the second solid electrolyte layer 13 as a porous layer can be made to be less likely to be peeled off from the first solid electrolyte layer 12.
[0081] In the present invention, the average particle size is the average particle size (D 50In the examples of this specification, a laser diffraction particle size distribution measuring device, product number "SALD-2200" manufactured by Shimadzu Corporation, was used to measure the average particle size (D 50 ).
[0082] Next, an organic vehicle is added to at least one of the prepared first solid electrolyte powder and the raw material powder of the first solid electrolyte powder to prepare a slurry. The organic vehicle includes a binder. As the binder, for example, a resin binder such as polypropylene carbonate can be used.
[0083] In addition, the binder may be a glass binder. As the glass binder, for example, sodium ion conductive glass powder can be used.
[0084] The sodium ion conductive glass powder preferably contains 10 to 80% of Na in mol%. 2 O, 10% to 60% P 2 O 5 +B 2 O 3 +SiO 2 and 0% to 55% Al 2 O 3 +Y 2 O 3 +Yb 2 O 3 +Nd 2 O 3 +Nb 2 O 5 +V 2 O 5 +TiO 2 +HfO 2 +ZrO 2 +MgO+CaO+BaO. The reason for limiting the glass composition in this way is described below. In the following description of the content of each component, "%" means "mol %" unless otherwise specified.
[0085] Na 2 O is a component that forms a sodium ion conduction path. In addition, it has the effect of lowering the melting temperature and softening point. By lowering the softening point, the raw material powder can be sintered at a low temperature (for example, below 1000°C). 2 The content of O is preferably 10% to 80%, more preferably 15% to 75%, further preferably 20% to 70%, particularly preferably 30% to 60%, and most preferably 40% to 60%. 2 If the content of O is too low, the sodium ion conductivity of the solid electrolyte is likely to decrease. 2 If the content of O is too low, it is difficult to obtain a dense sintered body.2 When the content of O is too large, weather resistance tends to decrease.
[0086] P 2 O 5 , B 2 O 3 and SiO 2 It is a network-forming component and has the effect of improving chemical durability. In addition, by including these components, when the raw material powder is sintered, the glass powder is easily fused with the sodium ion conductive crystal powder, and a sodium ion conductive path is easily formed between the sodium ion conductive crystal particles.
[0087] P 2 O 5 , B 2 O 3 and SiO 2 The total content of P is preferably 10% to 60%, more preferably 15% to 55%, and further preferably 20% to 50%. 2 O 5 , B 2 O 3 and SiO 2 When the content of P is too small, it is difficult to obtain the above-mentioned effect. 2 O 5 , B 2 O 3 and SiO 2 When the content of Na is too high, 2 O content is relatively low, and sodium ion conductivity is likely to decrease. 2 O 5 , B 2 O 3 and SiO 2 It is preferred to use P 2 O 5 and SiO 2 , it is more preferred to use P 2 O 5 In this case, the sodium ion conductivity of the solid electrolyte can be further improved.
[0088] Al 2 O 3 , Y 2 O 3 , Yb 2 O 3 、Nd 2 O 3 , Nb 2 O 5 、V 2 O 5 、TiO 2 , HfO 2 、ZrO2 , MgO, CaO, BaO and other components are components that stabilize the glass transition and are also components that improve the sodium ion conductivity. In addition, by including these components, when the raw material powder is sintered, the glass powder is easily dissolved in the sodium ion conductive crystal powder, and a sodium ion conductive path between the sodium ion conductive crystal particles is easily formed. As a result, the sodium ion conductivity of the solid electrolyte is also easily improved. The content of these other components is preferably 0% to 55% in total, more preferably 0.1% to 50%, further preferably 0.5% to 40%, further more preferably 1% to 40%, particularly preferably 5% to 40%, and most preferably 10% to 40%. When the content of these other components is too much, there is a tendency for the glass transition to become unstable. Among these other components, Nb is preferably used. 2 O 5 , Y 2 O 3 and V 2 O 5 , preferably using Nb 2 O 5 In this case, the sodium ion conductivity of the solid electrolyte can be further improved.
[0089] The organic vehicle may contain a solvent, a plasticizer, etc. in addition to the binder. As the solvent, for example, water or an organic solvent such as ethanol or acetone can be used. However, when water is used as the solvent, alkaline components such as sodium are dissolved from the raw material powder, the pH of the slurry rises, and the raw material powder is likely to condense. Therefore, it is preferred to use an organic solvent as the solvent.
[0090] The content of at least one of the first solid electrolyte powder and the raw material powder of the first solid electrolyte powder contained in the slurry is preferably 10% by mass or more, more preferably 30% by mass or more, preferably 80% by mass or less, and more preferably 50% by mass or less. In addition, the content of the binder contained in the slurry can be set to, for example, 5% by mass or more and 50% by mass or less.
[0091] Next, the obtained slurry is applied to a substrate and dried. The substrate is not particularly limited, and for example, a resin film such as a PET (polyethylene terephthalate) film can be used. In addition, the drying temperature of the slurry can be, for example, 40° C. to 100° C. The drying time of the slurry can be, for example, 3 minutes to 24 hours.
[0092] Next, the dried slurry is peeled off from the substrate to obtain Figure 1 (a) shows a first solid electrolyte layer forming green sheet 2.
[0093] (b) Preparation of Green Sheet for Forming Second Solid Electrolyte Layer
[0094] First, prepare a second solid electrolyte powder. Alternatively, a raw material powder of the second solid electrolyte powder (a powder that reacts in a subsequent firing step to become a solid electrolyte) may be prepared instead of the second solid electrolyte powder. Alternatively, a mixed powder of the second solid electrolyte powder and the raw material powder of the second solid electrolyte powder may be prepared.
[0095] The average particle size of at least one of the second solid electrolyte powder and the raw material powder of the second solid electrolyte powder is preferably 0.1 μm or more, more preferably 0.2 μm or more, further preferably 0.5 μm or more, particularly preferably 0.8 μm or more, preferably 100 μm or less, more preferably 50 μm or less, further preferably 10 μm or less, further preferably 5 μm or less, particularly preferably 3 μm or less. In this case, in the subsequent firing step, the second solid electrolyte layer 13 as a porous layer can be made to be less likely to be peeled off from the first solid electrolyte layer 12.
[0096] The ratio of the average particle size of at least one of the second solid electrolyte powder and the raw material powder of the second solid electrolyte powder to the average particle size of at least one of the first solid electrolyte powder and the raw material powder of the first solid electrolyte powder (second solid electrolyte powder / first solid electrolyte powder) is preferably 1.01 or more, more preferably 1.1 or more, further preferably 1.5 or more, particularly preferably 2 or more, preferably 1000 or less, more preferably 100 or less, further preferably 10 or less. In this case, in the subsequent firing step, the second solid electrolyte layer 13 as a porous layer can be made less likely to be peeled off from the first solid electrolyte layer 12.
[0097] Among them, in addition to using powders with different average particle sizes as described above, the second solid electrolyte powder and at least one of the raw material powders of the second solid electrolyte powder can use the same powder as the powder described in the first solid electrolyte powder and at least one of the raw material powders of the first solid electrolyte powder.
[0098] Next, prepare polymer powder. The polymer powder is a material used to form voids in the obtained second solid electrolyte layer by burning and removing in the subsequent firing process. Examples of polymer powder include acrylic resin, polyacrylonitrile, polymethacrylonitrile or polystyrene. These polymer powders can be used alone or in combination.
[0099] The average particle size of the polymer powder is preferably 0.1 μm or more, more preferably 1 μm or more, further preferably 5 μm or more, particularly preferably 10 μm or more, preferably 100 μm or less, more preferably 80 μm or less, further preferably 70 μm or less, and particularly preferably 50 μm or less. If the average particle size of the polymer powder is too small, it is difficult to form three-dimensionally connected voids in the obtained second solid electrolyte layer. On the other hand, if the average particle size of the polymer powder is too large, the sintering of the obtained second solid electrolyte layer sometimes becomes insufficient, and the ion conductivity decreases.
[0100] The mixing ratio of the second solid electrolyte powder and at least one of the raw powders of the second solid electrolyte powder to the polymer powder is preferably 75:25 to 3:97 by volume, more preferably 60:40 to 6:94, and further preferably 40:60 to 9:91. If the content of the polymer powder is too little, it is difficult to form three-dimensionally connected voids in the obtained second solid electrolyte layer. On the other hand, if the content of the polymer powder is too much, the sintering of the obtained second solid electrolyte layer sometimes becomes insufficient, and the ion conductivity is reduced.
[0101] The content ratio of at least one of the second solid electrolyte powder and the raw material powder of the second solid electrolyte powder to the polymer powder is preferably 95:5 to 20:80, more preferably 90:10 to 30:70, and even more preferably 80:20 to 40:60 in terms of mass ratio.
[0102] Next, an organic vehicle is added to a mixed powder of at least one of the prepared second solid electrolyte powder and the raw material powder of the second solid electrolyte powder and the polymer powder to prepare a slurry. Among them, regarding other components added to the organic vehicle such as a binder, the same components as those described in the column of (a) Preparation of the green sheet for forming the first solid electrolyte layer can be used.
[0103] Among them, the content of at least one of the second solid electrolyte powder and the raw material powder of the second solid electrolyte powder contained in the slurry is preferably 5% by mass or more, more preferably 10% by mass or more, preferably 80% by mass or less, more preferably 60% by mass or less. In addition, the content of the binder contained in the slurry can be set to, for example, 5% by mass or more and 30% by mass or less.
[0104] Next, the obtained slurry is applied to a substrate and dried. The substrate is not particularly limited, and for example, a resin film such as a PET (polyethylene terephthalate) film can be used. In addition, the drying temperature of the slurry can be, for example, 40° C. to 100° C. The drying time of the slurry can be, for example, 5 minutes to 24 hours.
[0105] Next, the dried slurry is peeled off from the substrate to obtain Figure 1 (b) is a second solid electrolyte layer forming green sheet 3 shown.
[0106] (c) Preparation of laminate
[0107] Then, if Figure 1 As shown in (c), the second solid electrolyte layer forming green sheet 3 is stacked on the main surfaces 2a and 2b on both sides of the first solid electrolyte layer forming green sheet 2 to obtain a stacked body 4. However, the green sheets may be stacked and pressed by heating or the like to obtain the stacked body 4. In this case, the adhesion between the green sheets can be further improved.
[0108] (d) Firing of laminated body
[0109] Next, the obtained laminated body 4 is fired. Figure 1 As shown in (d), the first solid electrolyte layer 12 is formed, and the second solid electrolyte layer 13 is formed. In this way, a solid electrolyte sheet 10 can be obtained in which the second solid electrolyte layer 13 as a porous layer is provided on the main surfaces 12a and 12b on both sides of the first solid electrolyte layer 12 as a dense layer.
[0110] When forming the first solid electrolyte layer 12, the binder in the first solid electrolyte layer-forming green sheet 2 is preferably removed. When forming the second solid electrolyte layer 13, the binder and polymer particles in the second solid electrolyte layer-forming green sheet 3 are preferably removed.
[0111] The firing temperature can be appropriately selected according to the type of solid electrolyte powder (raw material powder) used. When the solid electrolyte powder contains β-alumina or β″-alumina, the firing temperature is preferably above 1300°C, more preferably above 1400°C, further preferably above 1500°C, preferably below 1800°C, and more preferably below 1700°C. When the firing temperature is too low, there is a tendency for sintering to become insufficient. Alternatively, the reaction of the raw material powder becomes insufficient, and it is difficult to generate the desired crystals. On the other hand, when the firing temperature is too high, the evaporation amount of the sodium component and the like increases, heterogeneous crystals precipitate, and the ion conductivity of the obtained solid electrolyte sheet 10 is easily reduced.
[0112] In the case where the solid electrolyte powder contains NASICON crystals, the firing temperature is preferably above 900°C, more preferably above 1000°C, preferably below 1400°C, and more preferably below 1300°C. When the firing temperature is too low, there is a tendency for sintering to become insufficient. Or the reaction of the raw material powder becomes insufficient, and it is difficult to generate the desired crystals. On the other hand, when the firing temperature is too high, the evaporation amount of sodium components, etc. increases, heterogeneous crystals precipitate, and the ion conductivity of the solid electrolyte sheet 10 is easily reduced.
[0113] The firing time is appropriately adjusted so that sintering proceeds sufficiently, and specifically, it is preferably 5 minutes to 600 minutes, and particularly preferably 10 minutes to 300 minutes.
[0114] In addition, in the above-mentioned embodiment, the second solid electrolyte layer 13 as a porous layer is formed on the main surfaces 12a and 12b on both sides of the first solid electrolyte layer 12 as a dense layer, but the second solid electrolyte layer 13 as a porous layer may be formed only on the first main surface 12a of the first solid electrolyte layer 12 as a dense layer, or the second solid electrolyte layer 13 as a porous layer may be formed only on the second main surface 12b of the first solid electrolyte layer 12 as a dense layer.
[0115] The obtained solid electrolyte sheet 10 can be suitably used in all-solid-state batteries such as all-solid-state sodium ion secondary batteries and all-solid-state lithium ion secondary batteries. Among them, the solid electrolyte sheet 10 can be more suitably used in all-solid-state sodium ion secondary batteries.
[0116] [Solid electrolyte sheet]
[0117] Figure 2 Schematic cross-sectional view showing a solid electrolyte sheet according to one embodiment of the present invention. Figure 2 As shown, the solid electrolyte sheet 10 includes a first solid electrolyte layer 12 and a second solid electrolyte layer 13 .
[0118] The first solid electrolyte layer 12 has a first main surface 12a and a second main surface 12b facing each other. The second solid electrolyte layer 13 is provided on the first main surface 12a of the first solid electrolyte layer 12. In addition, the second solid electrolyte layer 13 is also provided on the second main surface 12b of the first solid electrolyte layer 12. Therefore, in the solid electrolyte sheet 10, the second solid electrolyte layer 13 is provided on the main surfaces 12a and 12b on both sides of the first solid electrolyte 12.
[0119] In the solid electrolyte sheet 10 , the average crystal grain size of the first solid electrolyte constituting the first solid electrolyte layer 12 is smaller than the average crystal grain size of the second solid electrolyte constituting the second solid electrolyte layer 13 .
[0120] Such a solid electrolyte sheet 10 can be manufactured, for example, by the above-mentioned method for manufacturing the solid electrolyte sheet 10. Therefore, in the solid electrolyte sheet 10, the shrinkage of the sheet is suppressed in the firing process when the sheet is formed. Therefore, even in the case where the solid electrolyte sheet 10 is extremely thin, it is not easy to shrink unevenly in the surface, and it is not easy to cause undulation and warping. Therefore, the solid electrolyte sheet 10 is excellent in handleability and is not easy to reduce strength.
[0121] The average crystal grain size of the first solid electrolyte is preferably 0.01 μm or more, more preferably 0.05 μm or more, further preferably 0.1 μm or more, preferably 10 μm or less, more preferably 5 μm or less, further preferably 3 μm or less, further preferably 1 μm or less, and particularly preferably 0.6 μm or less. In this case, the uniformity and smoothness of the green sheet of the solid electrolyte sheet 10 can be made more excellent during the forming, and the close contact during the stacking and the compactness during the firing can be further improved, so the handling property of the final solid electrolyte sheet 10 can be further improved.
[0122] The average crystal grain size of the second solid electrolyte is preferably 0.1 μm or more, more preferably 0.2 μm or more, further preferably 0.5 μm or more, particularly preferably 0.8 μm or more, most preferably 1.0 μm or more, preferably 100 μm or less, more preferably 50 μm or less, further preferably 10 μm or less, further preferably 5 μm or less, particularly preferably 3 μm or less, and most preferably 2 μm or less. In this case, the uniformity and smoothness of the green sheet of the second solid electrolyte can be made more excellent during molding, the adhesion during stacking and the density of the skeleton of the solid electrolyte during firing can be improved, so the operability of the final solid electrolyte sheet 10 can be improved.
[0123] The average crystal grain sizes of the first solid electrolyte and the second solid electrolyte can be measured, for example, as follows.
[0124] First, a sample of the solid electrolyte sheet 10 is broken to form a cross section. Next, the sample is heat treated. The heat treatment is preferably performed by heat etching in an electric furnace. The heat treatment temperature can be set to, for example, 900° C. or more and 1600° C. or less. The heat treatment time can be set to, for example, 1 minute or more and 60 minutes or less.
[0125] Next, a scanning electron microscope (SEM) is used to observe the cross section of the heat-treated sample. For example, any 200 particles in the obtained SEM image are counted by image analysis software to obtain the average particle size. Thus, the average crystal particle size of the first solid electrolyte and the second solid electrolyte can be obtained. In addition, in the image analysis, the area circle equivalent diameter of the grain is used as the particle size.
[0126] In the solid electrolyte sheet 10 of the present embodiment, the first solid electrolyte layer 12 as a dense layer and the second solid electrolyte layer 13 as a porous layer are integrated. In addition, in the solid electrolyte sheet 10 of the present embodiment, the thickness of the second solid electrolyte layer 13 is thicker than the thickness of the first solid electrolyte layer 12. As in the present embodiment, it is preferred that the first solid electrolyte layer 12 as a dense layer and the second solid electrolyte layer 13 as a porous layer are integrated, and the thickness of the second solid electrolyte layer 13 is thicker than the thickness of the first solid electrolyte layer 12, but it is not particularly limited.
[0127] Among them, the thickness of the solid electrolyte sheet 10 is not particularly limited, but is preferably greater than 1 μm, more preferably greater than 5 μm, further preferably greater than 10 μm, particularly preferably greater than 20 μm, preferably less than 1000 μm, more preferably less than 800 μm, further preferably less than 500 μm, particularly preferably less than 300 μm, and most preferably less than 200 μm.
[0128] When the thickness of the solid electrolyte sheet 10 is above the above lower limit, the mechanical strength can be further improved, and the short circuit between the positive electrode and the negative electrode can be made more difficult to occur. In addition, when the thickness of the solid electrolyte sheet 10 is below the above upper limit, the distance required for ion conduction in the solid electrolyte becomes shorter, and the ion conductivity is further improved. In addition, when used as a solid electrolyte sheet for an all-solid-state battery, the energy density per unit volume of the all-solid-state battery can be further improved.
[0129] In the solid electrolyte sheet 10, the film thickness ratio of the second solid electrolyte layer 13 to the first solid electrolyte layer 12 (second solid electrolyte layer 13 / first solid electrolyte layer 12) is preferably 1.01 or more, more preferably 1.1 or more, and preferably 1000 or less, more preferably 100 or less. In this case, the shrinkage of the solid electrolyte sheet 10 can be further suppressed in the firing process when the sheet is formed. In addition, the adhesion between the solid electrolyte sheet 10 and the electrode layer can be further improved.
[0130] The flatness of the solid electrolyte sheet 10 is preferably 200 μm or less, more preferably 100 μm or less, and further preferably 50 μm or less. In this case, the operability of the solid electrolyte sheet 10 can be further improved, and cracks during electrode formation can be made less likely to occur. The lower limit of the flatness of the solid electrolyte sheet 10 is not particularly limited, and can be set to 0.1 μm, for example.
[0131] In addition, flatness is defined in JIS B0621-1984 as “the degree to which a planar shape deviates from a geometrically correct plane.” The flatness of the solid electrolyte sheet 10 indicates the value of a gap formed when one surface of the sheet is sandwiched between parallel planes.
[0132] Among them, in the present invention, the second solid electrolyte layer 13 may be provided on at least one main surface 12a, 12b of the first solid electrolyte layer 12, but it is preferred that the second solid electrolyte layer 13 is provided on the main surfaces 12a, 12b of both sides of the first solid electrolyte layer 12 as in the present embodiment. In this case, since both surfaces of the solid electrolyte sheet 10 are composed of the second solid electrolyte layer 13, when the solid electrolyte sheet 10 is used in an all-solid-state battery, the adhesion with both the positive electrode layer and the negative electrode layer can be improved.
[0133] Hereinafter, each layer constituting the solid electrolyte sheet 10 will be described in detail.
[0134] (First solid electrolyte layer)
[0135] The first solid electrolyte layer 12 not only has the original role of the solid electrolyte, but also functions as a base layer for ensuring the mechanical strength of the solid electrolyte sheet 10. Therefore, the first solid electrolyte layer 12 has a denser structure than the second solid electrolyte layer 13.
[0136] The first solid electrolyte layer 12 preferably has a smaller porosity than the second solid electrolyte layer 13. In addition, the porosity of the first solid electrolyte layer 12 defined by the following formula (1) is preferably 20% or less, more preferably 10% or less, and further preferably 5% or less. The lower limit of the porosity is not particularly limited, and can be, for example, 0.1%.
[0137] Void ratio = (1-p / p0) × 100 (%) ... Formula (1)
[0138] In formula (1), p is the volume density and p0 is the true density.
[0139] When the solid electrolyte sheet 10 is used for an all-solid-state sodium ion secondary battery, as the material of the first solid electrolyte layer 12, for example, at least one selected from β″-alumina, β-alumina, and NASICON crystal can be used.
[0140] In addition, when the solid electrolyte sheet 10 is used for an all-solid-state lithium-ion secondary battery, as the material of the first solid electrolyte layer 12, for example, a material selected from La 0.51 Li 0.34 Ti 2.94 , Li 1.3 Al 0.3 Ti 1.7 (PO4 ) 3 , Li 7 La 3 Zr 2 O 12 , Li 1.07 Al 0.69 Ti 1.46 (PO 4 ) 3 , Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 At least one of .
[0141] As these materials, the same materials as those described in the section (a) Preparation of the Green Sheet for Forming the First Solid Electrolyte Layer can be used.
[0142] The thickness of the first solid electrolyte layer 12 is preferably 0.01 μm or more, more preferably 0.1 μm or more, further preferably 1 μm or more, particularly preferably 5 μm or more, preferably 300 μm or less, more preferably 200 μm or less, further preferably 150 μm or less, and particularly preferably 100 μm or less. If the thickness of the first solid electrolyte layer 12 is too small, the mechanical strength may be reduced, or the positive electrode and the negative electrode may be short-circuited. On the other hand, if the thickness of the first solid electrolyte layer 12 is too large, the ion conductivity of the solid electrolyte sheet 10 is easily reduced. In addition, when the solid electrolyte sheet 10 is used in an all-solid-state battery, there is a tendency for the energy density per unit volume of the all-solid-state battery to increase.
[0143] (Second Solid Electrolyte Layer)
[0144] The second solid electrolyte layer 13 is a porous layer having voids that are three-dimensionally connected to the solid electrolyte. In the case of using the solid electrolyte sheet 10 to make an all-solid-state battery, an electrode layer (positive electrode layer or negative electrode layer) is formed on the main surfaces 13a, 13b of the second solid electrolyte layer 13. At this time, the second solid electrolyte layer 13 has voids that are three-dimensionally connected, so the materials (active material powder, etc.) that constitute the electrode layer can easily enter the voids. Therefore, by providing the second solid electrolyte layer 13 as a porous layer on the first solid electrolyte layer 12 as a dense layer, the close contact between the solid electrolyte sheet 10 and the electrode layer can be improved.
[0145] The porosity of the second solid electrolyte layer 13 defined by the above formula (1) is preferably 25% or more, more preferably 30% or more, further preferably 40% or more, preferably 97% or less, more preferably 95% or less, further preferably 90% or less. When the porosity of the second solid electrolyte layer 13 is within the above range, it is easier to form three-dimensionally connected voids, and the adhesion between the solid electrolyte sheet 10 and the electrode layer can be further improved.
[0146] The diameter of the pores present in the second solid electrolyte layer 13 is preferably 0.1 μm or more, more preferably 0.5 μm or more, further preferably 1 μm or more, preferably 100 μm or less, more preferably 80 μm or less, further preferably 60 μm or less. In this case, the shrinkage of the solid electrolyte sheet 10 can be further suppressed during the firing step when the sheet is formed.
[0147] The diameter of the pores in the second solid electrolyte layer 13 can be measured by observing the 3D structure using X-ray CT and analyzing the image. Alternatively, it can be determined by measuring using mercury intrusion porosimetry or 3D reconstruction using SEM-FIB.
[0148] In addition, if Figure 4 As shown, the second solid electrolyte layer 13 preferably has pores having a diameter larger than the thickness of the first solid electrolyte layer 12. In this case, the shrinkage of the solid electrolyte sheet 10 can be further suppressed during the firing process when the sheet is formed. Figure 4 is a scanning electron microscope photograph of a solid electrolyte sheet 10 produced in Example 1 described later. Figure 4 In the embodiment, a solid electrolyte sheet 10 is formed in which a second solid electrolyte layer 13 as a porous layer is provided on both main surfaces 12a and 12b of a first solid electrolyte layer 12 as a dense layer.
[0149] When the solid electrolyte sheet 10 is used for an all-solid-state sodium ion secondary battery, as the material of the second solid electrolyte layer 13, for example, at least one selected from β″-alumina, β-alumina, and NASICON crystal can be used.
[0150] As these materials, the same materials as those described in the section (a) Preparation of the Green Sheet for Forming the First Solid Electrolyte Layer can be used.
[0151] In addition, when the solid electrolyte sheet 10 is used for an all-solid-state lithium-ion secondary battery, as the material of the second solid electrolyte layer 13, for example, a material selected from La 0.51 Li 0.34 Ti 2.94 , Li 1.3 Al0.3 Ti 1.7 (PO 4 ) 3 , Li 7 La 3 Zr 2 O 12 , Li 1.07 Al 0.69 Ti 1.46 (PO 4 ) 3 , Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 At least one of .
[0152] The thickness of the second solid electrolyte layer 13 is preferably 1 μm or more, more preferably 2 μm or more, further preferably 5 μm or more, particularly preferably 10 μm or more, preferably 1000 μm or less, more preferably 800 μm or less, further preferably 500 μm or less, particularly preferably 300 μm or less.
[0153] If the thickness of the second solid electrolyte layer 13 is too small, the amount of material constituting the electrode layer that enters the voids of the second solid electrolyte layer 13 is small, so the contact area between the solid electrolyte sheet 10 and the electrode layer becomes smaller, and the adhesion is easily reduced. In this case, the ion conduction path at the interface between the solid electrolyte sheet 10 and the electrode layer becomes smaller, so there is a tendency for the internal resistance of the battery to increase. As a result, the rapid charge and discharge characteristics are easily reduced.
[0154] On the other hand, if the thickness of the second solid electrolyte layer 13 is too large, it is difficult to fill the material constituting the electrode layer into the entire voids of the second solid electrolyte layer 13, and the energy density per unit volume becomes low. In addition, the amount of shrinkage when the second solid electrolyte layer 13 is formed becomes large, and the second solid electrolyte layer 13 is easily peeled off at the interface with the first solid electrolyte layer 12.
[0155] The arithmetic mean roughness Ra of the second solid electrolyte layer 13 (arithmetic mean roughness of the main surface 13a or the main surface 13b) is preferably 0.1 μm or more, more preferably 1 μm or more, further preferably 5 μm or more, preferably 300 μm or less, more preferably 200 μm or less, further preferably 100 μm or less. In this case, the adhesion between the solid electrolyte sheet 10 and the electrode layer can be further improved.
[0156] The second solid electrolyte layer 13 may also be composed of multiple layers with different porosities. In this case, the multiple layers with different porosities are preferably set so that the porosity of the layer closer to the first solid electrolyte layer 12 is lower. In addition, the number of multiple layers with different porosities is preferably 2 layers or more, more preferably 3 layers or more, further preferably 4 layers or more, particularly preferably 5 layers or more, preferably 200 layers or less, more preferably 150 layers or less, further preferably 100 layers or less, particularly preferably 50 layers or less, further more preferably 20 layers or less, and most preferably 10 layers or less.
[0157] A metal layer may also be provided on each of the main surfaces 13a and 13b of the second solid electrolyte layer 13. In particular, when the electrode layer formed on the second solid electrolyte layer 13 is made of a material such as metallic sodium or metallic lithium, by providing a metal layer between the second solid electrolyte layer 13 and the electrode layer, the wettability of the second solid electrolyte layer 13 and the electrode layer is improved, the adhesion is improved, and the interface resistance can be reduced. Thus, an all-solid-state battery with excellent discharge capacity can be obtained.
[0158] There is no particular limitation on the metal constituting the metal layer, and for example, Sn, Ti, Bi, Au, Al, Cu, Sb, Pb, etc. can be used. One of these metals constituting the metal layer can be used alone, or two or more of them can be used in combination. In addition, the metal layer can also be composed of an alloy of these metals.
[0159] The thickness of the metal layer is preferably 3 nm or more, more preferably 5 nm or more, further preferably 10 nm or more, particularly preferably 20 nm or more, and is preferably 5 μm or less, more preferably 3 μm or less, further preferably 1 μm or less, particularly preferably 500 nm or less.
[0160] As a method for forming the metal layer, for example, physical vapor phase methods such as vapor deposition or sputtering, chemical vapor phase methods such as thermal CVD, MOCVD, and plasma CVD, plating, sol-gel method, liquid phase film forming method based on spin coating, etc. can be listed. Among them, if vapor deposition or sputtering is used, it is easy to make the metal layer thin film, and it is easy to obtain the above-mentioned effect brought about by providing the metal layer, so it is preferred.
[0161] Hereinafter, the present invention will be described in more detail based on examples. However, the following examples are only illustrative and the present invention is not limited in any way by the following examples.
[0162] (Example 1)
[0163] (a) Preparation of Green Sheet for Forming First Solid Electrolyte Layer
[0164] To 100 parts by mass of NASICON (average particle size: 0.2 μm) as the first solid electrolyte powder, 15 parts by mass of polyvinyl butyral resin (manufactured by Sekisui Chemical Co., Ltd., trade name "S-LEC BM-SZ") as a binder were added, dispersed in N-methylpyrrolidone, and then fully stirred with a rotary mixer to form a slurry. The obtained slurry was applied to a PET film using a scraper, dried at 80°C, and then peeled off from the PET film to obtain a raw sheet for forming the first solid electrolyte layer. In addition, the composition of the NASICON crystals used was Na 3 Zr 2 Si 2 PO 12 .
[0165] (b) Preparation of Green Sheet for Forming Second Solid Electrolyte Layer
[0166] NASICON (average particle size: 2.0 μm) as the second solid electrolyte powder and cross-linked polymethyl methacrylate particles (manufactured by Sekisui Chemicals, product number "Techpolymer MBX-50", average particle size 50 μm) as polymer particles are weighed in a volume ratio of 1:5. 20 parts by mass of polyvinyl butyral resin (manufactured by Sekisui Chemical, trade name "S-LEC BM-SZ") as a binder are added to 100 parts by mass of these mixtures, dispersed in N-methylpyrrolidone, and then thoroughly stirred with a rotation / revolution mixer to form a slurry. The obtained slurry is applied to a PET film using a scraper, dried at 80°C, and then peeled off from the PET film to obtain a raw sheet for forming the second solid electrolyte layer. In addition, the composition of the NASICON crystals used is Na 3 Zr 2 Si 2 PO 12 .
[0167] (c) Preparation of laminate
[0168] The obtained second solid electrolyte layer forming green sheet was stacked on both main surfaces of the obtained first solid electrolyte layer forming green sheet, and heat pressed at 90° C. for 5 minutes to produce a stacked body.
[0169] (d) Firing of laminated body
[0170] The obtained laminate was fired at 1100° C. for 4 hours to prepare a solid electrolyte sheet (thickness 200 μm) in which the second solid electrolyte layer as a porous layer was provided on both main surfaces of the first solid electrolyte layer as a dense layer.
[0171] Among them, in the obtained solid electrolyte sheet, the thickness of the first solid electrolyte layer is 20μm, and the thickness of the second solid electrolyte layer is 90μm. In addition, the porosity of the first solid electrolyte layer is 2%, and the porosity of the second solid electrolyte layer is 77%. In addition, the diameter of the pores existing in the second solid electrolyte layer is 40μm.
[0172] (Examples 2 to 6)
[0173] A solid electrolyte sheet was prepared in the same manner as in Example 1 except that NASICON having the average particle diameter shown in Table 1 below was used as the first solid electrolyte powder and the second solid electrolyte powder.
[0174] Among them, in the solid electrolyte sheets obtained in Examples 2 to 6, the thickness of the first solid electrolyte layer, the thickness of the second solid electrolyte layer, the thickness of the solid electrolyte sheet, the porosity of the first solid electrolyte layer, the porosity of the second solid electrolyte layer, and the diameter of the pores present in the second solid electrolyte layer are as shown in Table 1 below.
[0175] (Comparative Example 1)
[0176] The green sheet for forming the first solid electrolyte layer produced by the same method as in Example 1 was fired at 1100° C. for 4 hours as it was, thereby producing a solid electrolyte sheet (thickness 20 μm) consisting only of the first solid electrolyte layer as a dense layer.
[0177] In the obtained solid electrolyte sheet, the porosity of the first solid electrolyte layer was 2%.
[0178] (Comparative Example 2)
[0179] A solid electrolyte sheet (thickness 180 μm) was prepared in the same manner as in Example 1 except that NASICON having an average particle size of 2.0 μm was used as the first solid electrolyte powder.
[0180] Among them, in the obtained solid electrolyte sheet, the thickness of the first solid electrolyte layer is 20μm, and the thickness of the second solid electrolyte layer is 80μm. In addition, the porosity of the first solid electrolyte layer is 2%, and the porosity of the second solid electrolyte layer is 80%. In addition, the diameter of the pores existing in the second solid electrolyte layer is 20μm.
[0181] (Comparative Example 3)
[0182] The green sheet for forming the first solid electrolyte layer produced by the same method as in Example 2 was directly fired at 1100°C for 4 hours to produce a solid electrolyte sheet consisting only of the first solid electrolyte layer as a dense layer. In the obtained solid electrolyte sheet, the porosity of the first solid electrolyte layer is as shown in Table 2 below.
[0183] (Comparative Example 4)
[0184] The green sheet for forming the first solid electrolyte layer produced by the same method as in Example 3 was directly fired at 1100°C for 4 hours to produce a solid electrolyte sheet consisting only of the first solid electrolyte layer as a dense layer. In the obtained solid electrolyte sheet, the porosity of the first solid electrolyte layer is as shown in Table 2 below.
[0185] Figure 3 This is a scanning electron microscope photograph of the surface of the solid electrolyte sheet produced in Example 1 at a magnification of 500 times. Figure 4 This is a scanning electron microscope photograph of a cross section of the solid electrolyte sheet produced in Example 1 at a magnification of 500 times. Figure 5 This is a scanning electron microscope photograph of a cross section of the solid electrolyte sheet produced in Example 1 at a magnification of 2000 times. Figure 7 This is a scanning electron microscope photograph at a magnification of 500 times of a cross section of a solid electrolyte sheet produced in Comparative Example 1. As a scanning electron microscope, a product number “S-3400N” manufactured by Hitachi High-Technologies Corporation was used.
[0186] according to Figure 3 to Figure 5 It can be seen that in Example 1, a solid electrolyte sheet is formed in which the second solid electrolyte layer as a porous layer is provided on both main surfaces of the first solid electrolyte layer as a dense layer. Figure 7 It is found that in Comparative Example 1, the second solid electrolyte layer, which is a porous layer, is separated from the first solid electrolyte layer, which is a dense layer.
[0187] Figure 6 2 is a photograph showing the appearance of the solid electrolyte sheet produced in Example 1 before and after firing. Figure 8 These are photographs showing the appearance of the solid electrolyte sheet produced in Comparative Example 1 before and after firing.
[0188] like Figure 6 As shown in FIG. 1 , the shrinkage rate of the solid electrolyte sheet of Example 1 during firing is 13%. Figure 8 As shown in FIG. 1 , the shrinkage rate during firing of the solid electrolyte sheet of Comparative Example 1 is 23%. Thus, it can be confirmed that the solid electrolyte sheet of Example 1 has suppressed shrinkage during firing compared with the solid electrolyte sheet of Comparative Example 1.
[0189] In the embodiments and comparative examples, the shrinkage rate is measured as follows. A green sheet or laminate for forming a solid electrolyte layer is punched into a φ20 mm sample using a manual punch, and the sample is fired under the above conditions. The diameter of the fired sample is measured, and the difference between the diameter of the sample before firing (20 mm) and the diameter measured after firing is obtained, and the ratio of the difference to the diameter of the sample before firing (20 mm) is taken as the shrinkage amount.
[0190] In addition, in Examples and Comparative Examples, the average crystal grain size of the first solid electrolyte constituting the first solid electrolyte layer and the average crystal grain size of the second solid electrolyte constituting the second solid electrolyte layer were measured by the following method.
[0191] First, a fractured cross section of a sample of a solid electrolyte sheet was formed. Next, the sample was subjected to heat treatment. The heat treatment was performed by heat etching at 1000° C. for 10 minutes using an electric furnace.
[0192] Next, a scanning electron microscope (SEM, Hitachi High-Tech Corporation, product number "S-3400NType II") was used to observe the cross section of the heat-treated sample. For any 200 particles in the obtained SEM image, the size of each particle was counted by image analysis software (Image J), thereby obtaining the average crystal grain size of the first solid electrolyte and the second solid electrolyte. In image analysis, the area circle equivalent diameter of the grain is used as the particle size.
[0193] Fig. 9 This is a scanning electron microscope photograph of a cross section of the first solid electrolyte layer after thermal etching of the solid electrolyte sheet produced in Example 1, at a magnification of 10,000 times. Fig.10 This is a scanning electron microscope photograph of a cross section of the second solid electrolyte layer after thermal etching of the solid electrolyte sheet produced in Example 1, at a magnification of 10,000 times.
[0194] like Fig. 9 and Fig.10 As shown, in the solid electrolyte sheet produced in Example 1, the average crystal grain size of the first solid electrolyte is smaller than the average crystal grain size of the second solid electrolyte.
[0195] The evaluation results of Examples 1 to 6 and Comparative Examples 1 to 4 are shown in Tables 1 and 2 below.
[0196] [Table 1]
[0197]
[0198] [Table 2]
[0199]
[0200] As shown in Table 1, in the solid electrolyte sheets obtained in Examples 1 to 6, the average crystal grain size of the first solid electrolyte is smaller than the average crystal grain size of the second solid electrolyte, the shrinkage during firing is reduced, and undulation or warping is suppressed. In addition, in the solid electrolyte sheets obtained in Examples 1 to 6, it can be confirmed that the operability is excellent and the strength is not easily reduced. On the other hand, as shown in Table 2, in the solid electrolyte sheets obtained in Comparative Examples 1, 3, and 4, since the second solid electrolyte layer is not formed, the shrinkage during firing is large, resulting in undulation or warping. In addition, in the solid electrolyte sheet obtained in Comparative Example 2, the average crystal grain size of the first solid electrolyte is the same as the average crystal grain size of the second solid electrolyte, and peeling occurs between the first solid electrolyte layer and the second solid electrolyte layer.
[0201] (Example 7)
[0202] (a) Preparation of Green Sheet for Forming First Solid Electrolyte Layer
[0203] To 100 parts by mass of β″-alumina (average particle size 0.4 μm) as the first solid electrolyte powder, 15 parts by mass of polyvinyl butyral resin (manufactured by Sekisui Chemical Co., Ltd., trade name “S-LEC BM-SZ”) as a binder was added, dispersed in N-methylpyrrolidone, and then fully stirred with a rotary mixer to form a slurry. The obtained slurry was applied to a PET film using a scraper, dried at 80°C, and then peeled off from the PET film, thereby obtaining a raw sheet for forming the first solid electrolyte layer. The composition of the β″-alumina used was Na 1.65 Al 10.35 Mg 0.65 O 17 .
[0204] (b) Preparation of Green Sheet for Forming Second Solid Electrolyte Layer
[0205] β″-alumina (average particle size 1.2 μm) as the second solid electrolyte powder and cross-linked polymethyl methacrylate particles (manufactured by Sekisui Chemicals Co., Ltd., product number "Techpolymer MBX-50", average particle size 50 μm) as polymer particles were weighed to a volume ratio of 1:4. To 100 parts by mass of these mixtures, 20 parts by mass of polyvinyl butyral resin (manufactured by Sekisui Chemical Co., Ltd., trade name "S-LEC BM-SZ") as a binder were added, dispersed in N-methylpyrrolidone, and then fully stirred with a rotation / revolution mixer to form a slurry. The obtained slurry was applied to a PET film using a scraper, dried at 80°C, and then peeled off from the PET film to obtain a raw sheet for forming the second solid electrolyte layer. In addition, the composition of the β″-alumina used was Na 1.65 Al 10.35 Mg 0.65 O 17 .
[0206] (c) Preparation of laminate
[0207] The second solid electrolyte layer forming green sheet was stacked on both main surfaces of the first solid electrolyte layer forming green sheet, and heat pressed at 90° C. for 5 minutes to produce a stacked body.
[0208] (d) Firing of laminated body
[0209] The obtained laminate was fired at 1550° C. for 30 minutes to prepare a solid electrolyte sheet (thickness 180 μm) in which the second solid electrolyte layer as a porous layer was provided on both main surfaces of the first solid electrolyte layer as a dense layer.
[0210] Among them, in the obtained solid electrolyte sheet, the thickness of the first solid electrolyte layer is 20μm, and the thickness of the second solid electrolyte layer is 80μm. In addition, the porosity of the first solid electrolyte layer is 2%, and the porosity of the second solid electrolyte layer is 75%. In addition, the diameter of the pores existing in the second solid electrolyte layer is 40μm.
[0211] (Example 8)
[0212] A solid electrolyte sheet (thickness 120 μm) was prepared in the same manner as in Example 7, except that β″-alumina (average particle size 1.2 μm) as the second solid electrolyte powder and cross-linked polymethyl methacrylate particles (manufactured by Sekisui Chemicals Co., Ltd., product number “Techpolymer SSX-120”, average particle size 20 μm) as polymer particles were weighed in a volume ratio of 1:5 to prepare a raw sheet for forming a second solid electrolyte layer.
[0213] Among them, in the obtained solid electrolyte sheet, the thickness of the first solid electrolyte layer is 20μm, and the thickness of the second solid electrolyte layer is 50μm. In addition, the porosity of the first solid electrolyte layer is 2%, and the porosity of the second solid electrolyte layer is 78%. In addition, the diameter of the pores existing in the second solid electrolyte layer is 15μm.
[0214] (Comparative Example 5)
[0215] The green sheet for forming the first solid electrolyte layer produced by the same method as in Example 7 was fired at 1550° C. for 30 minutes as it was, thereby producing a solid electrolyte sheet (thickness 20 μm) consisting only of the first solid electrolyte layer as a dense layer.
[0216] In the obtained solid electrolyte sheet, the porosity of the first solid electrolyte layer was 1%.
[0217] In addition, in Example 7, Example 8 and Comparative Example 5, the average crystal grain size of the first solid electrolyte constituting the first solid electrolyte layer and the average crystal grain size of the second solid electrolyte constituting the second solid electrolyte layer were measured using the same method as in Example 1, except that the heat treatment of the thermal etching was set to 1450°C for 10 minutes.
[0218] The shrinkage ratios of the solid electrolyte sheets produced in Examples 7 and 8 and Comparative Example 5 before and after firing are shown in Table 3 below.
[0219] [Table 3]
[0220]
[0221] As shown in Table 3, the shrinkage rates of the solid electrolyte sheets of Examples 7 and 8 during firing were 20% and 24%, respectively. On the other hand, as shown in Table 3, the shrinkage rate of the solid electrolyte sheet of Comparative Example 5 during firing was 26%. Thus, even in the case of using the solid electrolyte sheet of Example 2 in which the solid electrolyte was β″-alumina, it was confirmed that shrinkage during firing was suppressed.
[0222] Description of Reference Numerals
[0223] 2…Green sheet for forming the first solid electrolyte layer
[0224] 2a, 12a ... first main surface
[0225] 2b, 12b... second main surface
[0226] 3…Green sheet for forming the second solid electrolyte layer
[0227] 4…Laminated body
[0228] 10…Solid electrolyte sheet
[0229] 12…First solid electrolyte layer
[0230] 13…Second solid electrolyte layer
[0231] 13a, 13b…main surfaces.
Claims
1. A solid electrolyte sheet, comprising: a first solid electrolyte layer as a dense layer; and a second solid electrolyte layer as a porous layer provided on at least one main surface of the first solid electrolyte layer, An average crystal grain size of a first solid electrolyte constituting the first solid electrolyte layer is smaller than an average crystal grain size of a second solid electrolyte constituting the second solid electrolyte layer.
2. The solid electrolyte sheet according to claim 1, wherein: The second solid electrolyte layer is provided on both main surfaces of the first solid electrolyte layer.
3. The solid electrolyte sheet according to claim 1 or 2, wherein: The first solid electrolyte has an average crystal grain size of 0.01 μm or more and 10 μm or less.
4. The solid electrolyte sheet according to claim 1 or 2, wherein: The second solid electrolyte has an average crystal grain size of 0.1 μm or more and 100 μm or less.
5. The solid electrolyte sheet according to claim 1 or 2, wherein: The first solid electrolyte layer and the second solid electrolyte layer are integrated, The second solid electrolyte layer is thicker than the first solid electrolyte layer.
6. The solid electrolyte sheet according to claim 1 or 2, wherein: The second solid electrolyte layer has pores having a diameter larger than a thickness of the first solid electrolyte layer.
7. The solid electrolyte sheet according to claim 1 or 2, wherein: The diameter of the pores present in the second solid electrolyte layer is 0.1 μm or more and 100 μm or less.
8. The solid electrolyte sheet according to claim 1 or 2, wherein: The porosity of the second solid electrolyte layer is 25% or more and 97% or less.
9. The solid electrolyte sheet according to claim 1 or 2, wherein: At least one of the first solid electrolyte layer and the second solid electrolyte layer includes at least one selected from the group consisting of β″-alumina, β-alumina, and NASICON crystals.
10. The solid electrolyte sheet according to claim 1 or 2, wherein: Used in all-solid-state sodium-ion secondary batteries.
11. A method for manufacturing a solid electrolyte sheet, the solid electrolyte sheet comprising: a first solid electrolyte layer as a dense layer; and a second solid electrolyte layer as a porous layer provided on at least one main surface of the first solid electrolyte layer, the method for manufacturing the solid electrolyte sheet comprising: (a) adding an organic vehicle containing a binder to at least one of a first solid electrolyte powder and a raw material powder of the first solid electrolyte powder to prepare a slurry, applying the slurry on a substrate and drying the slurry to obtain a green sheet for forming a first solid electrolyte layer; (b) a step of adding an organic vehicle containing a binder to a mixed powder containing a second solid electrolyte powder and at least one of a raw material powder of the second solid electrolyte powder and a polymer powder to prepare a slurry, applying the slurry on a substrate and drying the slurry to obtain a green sheet for forming a second solid electrolyte layer; (c) a step of laminating the second solid electrolyte layer forming green sheet on at least one main surface of the first solid electrolyte layer forming green sheet to obtain a laminated body; and (d) a step of forming a first solid electrolyte layer as a dense layer and a second solid electrolyte layer as a porous layer by firing the stacked body, An average particle size of at least one of the first solid electrolyte powder and a raw material powder of the first solid electrolyte powder is smaller than an average particle size of at least one of the second solid electrolyte powder and a raw material powder of the second solid electrolyte powder.
12. The method for manufacturing a solid electrolyte sheet according to claim 11, wherein: The second solid electrolyte layer is formed on both main surfaces of the first solid electrolyte layer.
13. The method for producing a solid electrolyte sheet according to claim 11 or 12, wherein: An average particle size of at least one of the first solid electrolyte powder and a raw material powder of the first solid electrolyte powder is 0.01 μm or more and 10 μm or less.
14. The method for producing a solid electrolyte sheet according to claim 11 or 12, wherein: An average particle size of at least one of the second solid electrolyte powder and a raw material powder of the second solid electrolyte powder is 0.1 μm or more and 100 μm or less.
15. The method for manufacturing a solid electrolyte sheet according to claim 11 or 12, wherein: The polymer powder has an average particle size of 0.1 μm or more and 100 μm or less.
16. The method for manufacturing a solid electrolyte sheet according to claim 11 or 12, wherein: The mixing ratio of at least one of the second solid electrolyte powder and the raw material powder of the second solid electrolyte powder to the polymer powder is 75:25 to 3:97 in terms of volume ratio.
17. The method for manufacturing a solid electrolyte sheet according to claim 11 or 12, wherein: At least one of the first solid electrolyte layer and the second solid electrolyte layer includes at least one selected from the group consisting of β″-alumina, β-alumina, and NASICON crystals.
18. The method for manufacturing a solid electrolyte sheet according to claim 11 or 12, wherein: Used in all-solid-state sodium-ion secondary batteries.
Citation Information
Patent Citations
Solid electrolyte sheet and method for producing same
WO2021045039A1